Coccidioidomycosis Skin Testing in a Commercially Insured Population, United States, 2014–2017 - Kaitlin Benedict; Orion Z. McCotter; Brendan R. Jackson (Emerging Infectious Diseases, 2020)
Coccidioidomycosis skin testing appears to be uncommon, based on US health insurance claims data. Patient demographic features were consistent with the approval of the test for adults, but few patients had previous coccidioidomycosis diagnosis codes supporting its use for detecting delayed-type hypersensitivity in those with a history of pulmonary coccidioidomycosis.